Total synthesis of justicidin B, justicidin E, and taiwanin C: A general and flexible approach toward the synthesis of natural arylnaphthalene lactone lignans - Wei, Kai; Sun, Yucui; Xu, Yiren; Hu, Wen; Ma, Ying; Lu, Yi; Chen, Wen; Zhang, Hongbin (Frontiers in Chemistry, 2022)
Lignans are widely presented in the traditional medicine plants. A number of natural arylnaphthalene lactone lignans (NALLs) isolated from the genera Justicia, Haplophyllum and Phyllanthus possess interesting biological activities. Herein, we report a general strategy for the total synthesis of this kind of lignans. Features of this new approach are an aryl-alkyl Suzuki cross-coupling to introduce the dioxinone unit, a cation-induced cyclization to construct the aryl dihydronaphthalene and a base mediated oxidative aromatization to furnish the arylnaphthalene core. By incorporation of these key transformations, total syntheses of Justicidins B and E as well as Taiwanin C, covered type I and type II NALLs, were accomplished.